2020
DOI: 10.1038/s41467-020-16484-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-scale metabolic reconstruction of the symbiosis between a leguminous plant and a nitrogen-fixing bacterium

Abstract: The mutualistic association between leguminous plants and endosymbiotic rhizobial bacteria is a paradigmatic example of a symbiosis driven by metabolic exchanges. Here, we report the reconstruction and modelling of a genome-scale metabolic network of Medicago truncatula (plant) nodulated by Sinorhizobium meliloti (bacterium). The reconstructed nodule tissue contains five spatially distinct developmental zones and encompasses the metabolism of both the plant and the bacterium. Flux balance analysis (FBA) sugges… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 115 publications
7
60
0
Order By: Relevance
“…Of the 31 false negatives (in silico non-essential genes that were essential according to INSeq), nine were involved in sugar metabolism. In agreement with the results of a recent modelling study of S. meliloti 24 , this may suggest that rhizobia differentiating into bacteroids have access to sugars as a carbon source, whereas nitrogen-fixing bacteroids do not. In addition, four genes involved in serine metabolism were incorrectly predicted to be non-essential.…”
Section: Data-based Reconstruction Of a Bacteroid Metabolic Modelsupporting
confidence: 90%
See 2 more Smart Citations
“…Of the 31 false negatives (in silico non-essential genes that were essential according to INSeq), nine were involved in sugar metabolism. In agreement with the results of a recent modelling study of S. meliloti 24 , this may suggest that rhizobia differentiating into bacteroids have access to sugars as a carbon source, whereas nitrogen-fixing bacteroids do not. In addition, four genes involved in serine metabolism were incorrectly predicted to be non-essential.…”
Section: Data-based Reconstruction Of a Bacteroid Metabolic Modelsupporting
confidence: 90%
“…The copyright holder for this this version posted February 16, 2021. ; https://doi.org/10.1101/2021.02.16.431433 doi: bioRxiv preprint with an integrated plant-bacteroid model for S. meliloti 24 . Furthermore, less oxygen was needed for sucrose ( Fig.…”
Section: Metabolic Constraints On Ammonia Assimilation By Bacteroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational analyses revealed the costs and benefits of the symbiotic system for biomass growth when external ammonium is not available. Recently, the M. truncatula model was built to represent multi-organism metabolic interactions in different developmental zones within the nodule during nitrogen fixation (diCenzo et al, 2020). The multi-organism model consisted of M. truncatula nodulated by S. meliloti Rm1021.…”
Section: Metabolic Modeling and Metabolic Profiling Studies On Legumementioning
confidence: 99%
“…It was shown that when successful symbiosis is established, biological N 2 -fixation can supply the majority of the N required by host plants [ 100 ]. Flux balance analysis and a series of simulations using a “Virtual Nodule Environment” (ViNE) model of a genome-scale metabolic network in the SNF suggested that the metabolic costs associated with symbiotic N fixation are primarily related to supporting nitrogenase activity, and increasing N 2 -fixation efficiency is linked with decreasing returns in terms of the rate of plant growth [ 103 ].…”
Section: C and N Metabolism In The Presence Of Plant-microorganismmentioning
confidence: 99%